Conformational properties of nine purified cystathionine β-synthase mutants - Hnízda, Aleš; Majtan, Tomas; Liu, Lu; Pey, Angel L; Carpenter, John F; Kodíček, Milan; Kožich, Viktor; Kraus, Jan P (Biochemistry, 2012)
Protein misfolding due to missense mutations is a common pathogenic mechanism in cystathionine β-synthase (CBS) deficiency. In our previous studies, we successfully expressed, purified, and characterized nine CBS mutant enzymes containing the following patient mutations: P49L, P78R, A114V, R125Q, E176K, R266K, P422L, I435T, and S466L. These purified mutants exhibited full heme saturation, normal tetrameric assembly, and high catalytic activity. In this work, we used several spectroscopic and proteolytic techniques to provide a more thorough insight into the conformation of these mutant enzymes. Far-UV circular dichroism, fluorescence, and second-derivative UV spectroscopy revealed that the spatial arrangement of these CBS mutants is similar to that of the wild type, although the microenvironment of the chromophores may be slightly altered. Using proteolysis with thermolysin under native conditions, we found that the majority of the studied mutants is more susceptible to cleavage, suggesting their increased local flexibility or propensity for local unfolding. Interestingly, the presence of the CBS allosteric activator, S-adenosylmethionine (AdoMet), increased the rate of cleavage of the wild type and the AdoMet-responsive mutants, while the proteolytic rate of the AdoMet-unresponsive mutants was not significantly changed. Pulse proteolysis analysis suggested that the protein structure of the R125Q and E176K mutants is significantly less stable than that of the wild type and the other mutants. Taken together, the proteolytic data shows that the conformation of the pathogenic mutants is altered despite retained catalytic activity and normal tetrameric assembly. This study demonstrates that the proteolytic techniques are useful tools for the assessment of the biochemical penalty of missense mutations in CBS.
Keywords: Mutation, Missense; Proteolysis; cystathionin-beta-synthasa; Cystathionine beta-Synthase; Protein Folding; proteolýza; missense mutace; S-adenosylmethionin; Escherichia coli; sbalování proteinů; Circular Dichroism; molekulární modely; Models, Molecular; Spectrophotometry, Ultraviolet; lidé; S-Adenosylmethionine; konformace proteinů; Humans; cirkulární dichroismus; Protein Conformation; spektrofotometrie ultrafialová